84.7k views
0 votes
Question 2 please fas

Question 2 please fas-example-1

1 Answer

7 votes

Answer:

a = 3, b = 2

Explanation:

It is given that both the polynomials are equal.

Therefore, h(x) = k(x)


{x}^(3) + (a + b) {x}^(2) - 4x + 2 \\ = {x}^(3) + 5 {x}^(2) - (2a - b)x + 2 \\ \\ equating \: like \: terms \: on \: both \: sides \\ (a + b) {x}^(2) = 5 {x}^(2) \\ \implies \: a + b = 5.....(1) \\ \\ - (2a - b)x = - 4x \\ 2a - b = 4....(2) \\ \\ adding \: equations \: (1) \: and \: (2) \\ \\ 3a = 9 \\ \implies \: a = (9)/(3) \\ \huge \red{ \boxed{\implies \: a = 3}} \\ \\ substituting \: a = 3 \: in \: equation \: (1) \\ 3 + b = 5 \\ \implies \: b = 5 - 3 \\ \huge \purple{ \boxed{ \implies b = 2}}

User Numabyte
by
5.0k points